Democracy, local election, and political dynasty in Indonesian politics - Dede Mariana; Luthfi Hamzah Husin (JWP (Jurnal Wacana Politik), 2017)
Liberal democracy has been chosen as a model and political mechanism after Soeharto era. One of its triumphs is local election that becomes a political instrument of democratisation at regional level. Many scholars believe that local democratisation in Indonesia enables local people to involve more actively in the political process. This political exercise in some cases, however, results in a paradoxical impact on Indonesian political realm today, as some practices of political dynasty frequently emerge. Using participatory point of view, this article aims to discuss why such political dynasty can possibly emerge within an electoral system, what factors cause it and how its consequences on the practice of local democracy in Indonesia in the future. Through the literature studies, we argue that although the liberal democratisation in Indonesia is successful in making local politics institutionally more democratic, it still suffers a lot of deficiencies and limitations especially in terms of accommodating people’s participation at local level.